PENGARUH EXPERIENTIAL MARKETING TERHADAP KEPUTUSAN PEMBELIAN MAKAN DAN MINUMAN PADA PECEL LELE LELA DI KOTA PADANG - Maulina, Mia - (Pendidikan Ekonomi, 2014)
This study aims to analyze : 1 ) Influence Sense on purchasing decisions , 2 ) Feel Effect on purchase decisions , 3 ) Influence Think of purchasing decisions , 4 ) Effect of Act on purchasing decisions , 5 ) Effect Relate to the purchasing decision . This type of research is descriptive associative . The population was at Pecel Lele Lela customers in the city of Padang , the population in 3892 with a total of 97 samples . Data analysis techniques : a descriptive analysis , test specification models , the classical assumption test , multiple linear regression analysis , the coefficient of determination ( R Square ) and hypothesis testing . The results showed that : 1 ) There is a positive and significant effect between Sense on purchasing decisions with a regression coefficient of 5.501 t count > t table at 1.661 with significant value of 0.000 < Î± = 0.05 . 2 ) There is a positive and significant influence on purchasing decisions among Feel with regression coefficient of 2.240 tcount > ttable of 1.661 with significant value of 0.000 < Î± = 0.05 . 2 ) There is a positive and significant influence on purchasing decisions between Think koefiesien regression value of 2.037 t count > t table at 1.661 with significant value of 0.000 < Î± = 0.05 . 4 ) There is a positive and significant effect of the Act on purchasing decisions with a regression coefficient of 2.368 t count > t table at 1.661 with significant value of 0.000 < Î± = 0.05 . 5 ) There is a positive and significant influence on purchasing decisions among Relate kefisien regression value of 5.068 tcount > ttable of 1.661 with significant value of 0.000 < Î± = 0.05 . That is the good Sense , Feel , Think , Act and Relate it will better the effect on purchasing decisions . Pecel Lele Lela parties , in order to conduct a more in-depth analysis in terms of the application of the concept of purchasing decisions , because customers have different perceptions in determining choice in consuming . Researcher Furthermore, the expected results of this study can serve as a reference for further research that will address the same thing in other places . Furthermore , for those researchers who want to examine the influence on purchase decisions ekperiental marketing of food and drink at the restaurant